Strengthening Religious Education and Religious Literacy as Preventive Measures against Social Deviant Behavior in West Nusa Tenggara - Abdul Kadir Hairi Jaelani; Lalu Agus Murzaki; Sarwadi Sarwadi; Fuad Hasan; Sakarta Sakarta (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
This study investigates the role of Islamic Education (IE) in fostering family resilience in West Nusa Tenggara (NTB), where rapid social transformations challenge traditional moral frameworks. The research aims to explore how religious education and literacy serve as preventive measures against social deviant behavior. The study finds that IE, operationalized through Pesantren, Madrasah, and Majlis Taklim, integrates key theological values like tawakkul, sabr, and syukr into the daily lives of families, enhancing emotional regulation, coping capacity, and crisis management. Furthermore, religious literacy strengthens these effects by enabling individuals to apply moral principles in diverse social contexts. The research employs a qualitative approach with a normative-descriptive design, utilizing literature review and document analysis. The study contributes to expanding Family Resilience Theory (FRT) and Social Capital Theory (SCT) by incorporating a socio-theological perspective, highlighting the importance of institutional collaboration among families, schools, and religious organizations. The findings emphasize the need for educational reforms and suggest that integrating religious literacy into curricula can foster long-term moral resilience and social harmony.